2019
DOI: 10.1136/bmjopen-2018-028350
|View full text |Cite
|
Sign up to set email alerts
|

Population-based case–control study of the effect of sun glare on pedestrian fatalities in Taiwan

Abstract: ObjectivesSun glare is a serious driving hazard and increases crash risks. Relatively few studies have examined the effects of sun glare on pedestrian fatalities, given that a crash has occurred. The primary objective of this study was to investigate the effect of sun glare on pedestrian fatalities.DesignA population-based case–control study.SettingTaiwan.ParticipantsUsing the Taiwan National Traffic Crash Data and sunrise and sunset data from the National Oceanic and Atmospheric Administration for the period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This mix and the density of both pedestrians and PTWs translate to a high potential for unsafe interactions between the 2 types of road users 28 . The empirical results that sun glare is a combined spatiotemporal factor associated with pedestrian fatalities may be unique to Taiwan because of its unique sunrise and sunset times and orientations 29 . Younger patients, especially those with MVCs involving motorcycles in Chongqing, should be given more attention to prevent nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mix and the density of both pedestrians and PTWs translate to a high potential for unsafe interactions between the 2 types of road users 28 . The empirical results that sun glare is a combined spatiotemporal factor associated with pedestrian fatalities may be unique to Taiwan because of its unique sunrise and sunset times and orientations 29 . Younger patients, especially those with MVCs involving motorcycles in Chongqing, should be given more attention to prevent nerve injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Head injuries account for most pedestrian fatalities in crashes with powered 2-wheelers in India, and lower extremity injuries account for most nonfatal injuries 28 . Older pedestrians, male drivers, older drivers and intoxicated motorists are prevalent determinants of pedestrian fatalities in glare-related crashes 29 . Enhancing the conspicuity of pedestrians with the use of visibility aids may be beneficial for reducing crash risk or severity 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sun glare can occur in certain circumstances during this time and reduce visibility [100]. It was found that sun glare can lead to more severe injuries in pedestrian-related crashes [101]. This variable has a fixed effect in all other clusters, which shows the clustering method's efficacy in eliminating the heterogeneity for this variable.…”
Section: Temporal Characteristicsmentioning
confidence: 94%
“…Road environmental factors, namely weather conditions (adverse or fine weather), road light conditions (night-time or daytime), and road speed limit (≥50 km/h or <50 km/h), were analysed. Road light conditions were defined as “daytime” if crashes occurred between sunrise and sunset and “night-time” if crashes occurred between sunset and sunrise [ 22 , 26 ]. Data on sunrise and sunset times in Taiwan were obtained from the National Oceanic Earth System Research Laboratory and Atmospheric Administration database (accessed 2 February 2020).…”
Section: Methodsmentioning
confidence: 99%